Première van de film 'On the beach' in Alhambra met Mary Dresselhuys (midden) en Ko van Dijk - Meerendonk, Ben van,
Première van de film 'On the beach' in Alhambra met Mary Dresselhuys (midden) en Ko van Dijk.